"De ecclesia" - centon chrześcijański - Piątek, Mariusz (Vox Patrum, 2020)
Cento "De ecclesia" is one of four Christian centos which were compiled from Virgil’s work. This article examines the cento from the formal and the theological perspective. The first part discusses the authorship and structural issues. The second part demonstrates the theological diversity of the cento, which is full of Christological, soteriological, ecclesiological and eschatological questions. The use of the philological method and analysis of selected parts allowed us to establish how the author of the cento created his poem. He was inspired by the letter, context and characters appearing in Virgil’s works.